Testosterone and cortisol changes in professional basketball players through a season competition - Martinez, A. C.; Seco Calvo, J.; Tur Mari, J. A.; Abecia Inchaurregui, L. C.; Orella, E. E.; Biescas, A. P. (The Journal of Strength and Conditioning Research, 2010)
We analyze the outcome on testosterone (T) and cortisol (C) responses in 12 professional basketball players during a season of competition. Serum adrenocorticotropic hormone (ACTH), C, total testosterone (TT), and free testosterone (FT) levels were analyzed in October, December, March, and April. A day after the games, blood samples were taken. Serum ACTH levels were maintained at the initial levels during the season. However, basal C significantly changed during the season, with lower levels in December and in April. Basal serum TT levels increased during the season until a maximum in March. No differences were presented in the TT values in December, March, and April. Basal FT presented high levels in October and December, followed by a low level in March, remaining low in April. The T/C increased during the season, attaining a maximum level in December, followed by a significant decrease in March. Free T/C ratio decreased during the season (lower level in March). In conclusion, the players maintained a good anabolic-catabolic balance. In our opinion, to prevent the stress provoked during the season, and control the recovery periods, it is useful to monitor C, T, and the level of training.